Recursos didácticos en el área de lengua y literatura y su incidencia en el aprendizaje significativo de los estudiantes de cuarto año de básica de la Escuela Ciudad de Vinces, cantón Vinces, Provincia de Los Ríos - Echanique Fuentes, Catalina Leonor (2019)
Through this research was made and allowed to know the use of didactic resources in the area of Language and Literature and its impact on meaningful learning, since it facilitates a greater understanding of the topic that is going to be taught, because it makes the class more dynamic , when they are not used, learning problems are generated, because there are deficiencies in the development of the class, there is greater distraction in the students, boredom, in many cases they do not understand what will be the effect of poor school performance. In the present investigation the importance of the incidence was considered because it is fundamental for there to be a better interaction between the teacher and the student, with the use of the didactic resources in the significant learning in the area of Language and Literature, basic education can obtain better levels of learning, which will lead to them having a better training considering the different methodological aspects that are used in the classes to improve the educational process, making it more dynamic and motivating that allows the student to interact in classes.